(3fgL GdNGUs - (3CHhefUhQ eYeQ Hf CMeO Hf RjGO GdCUagGfjs
(3ChdgG (B:s
(3cJHJ EdjfG CHh efUhQ eYeQ Hf CMeO Hf RjGO GdCkUagGfj aj gPG GdcJGH GdoedbH HfgL GdNGU GdMeO ddg GdPj OYG GdNdb Edi faSg HGdBjGJ s
(3BNQgG (B:s
(3hGeG GdeYQaI HGdCag ddYGQajf ddMPQ aaj cd dMXI dge CaI hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B114 (3C (B- (3U(B130 (3Cs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B((3JUha (B1416(2)) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs